Game-Based Technologies as a Tool for Developing Communicative Competence in Primary School Students within a Student-Centered Educational Context - Bilous, Iryna; Shcherbiak, Iurii; Maslak, Volodymyr; Alnsour, Roa'a; Jarmoch , Edward Zygmunt; Hubková, Svetlana (Journal of Education Culture and Society, 2025)
Aim. The aim of the study is to determine the pedagogical potential of game-based technologies for developing communicative competence in primary school students, taking into account their individual psychological and sensory characteristics. Methods. The research methods include theoretical analysis (of scientific sources on communicative competence, game-based learning, developmental psychology), comparative review (of models by Dell Hymes, Michael Canale & Merrill Swain, Michael Halliday, Claire Kramsch), and empirical generalisation (of current international and Ukrainian practices in game-based learning). A typology of educational games was compiled (role-playing, dramatized, didactic), followed by the development of a model for adapting games to children’s individual characteristics (temperament, motivation, communication level, perception style). Specific examples of games and digital platforms (e.g., Wordwall, Toontastic, Classdojo) were analysed. Results. It was revealed that each type of game contributes to the development of certain components of communicative competence – linguistic, strategic, sociocultural, emotional. The adaptation model allows matching game formats to the Student’s personality profile, thereby increasing engagement, confidence, and social inclusion. Multimodal games enhance interaction through verbal and non-verbal means, while digital tools ensure differentiated learning paths. Conclusion. Game-based technologies serve as a powerful tool for developing communicative competence in primary education. Their correct adaptation provides an emotionally safe, inclusive, and interactive environment that supports both socialisation and language development in Students.